2019
DOI: 10.1021/jacs.8b12444
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Selective Minor Groove Recognition of a DNA Duplex Containing Synthetic Genetic Components

Abstract: The structural basis of minor groove recognition of a DNA duplex containing synthetic genetic information by hairpin pyrrole-imidazole polyamides is described. Hairpin polyamides induce a higher melting stabilization of a DNA duplex containing the unnatural P·Z base-pair when an imidazole unit is aligned with a P nucleotide. An NMR structural study showed that the incorporation of two isolated P·Z pairs enlarges the minor groove and slightly narrows the major groove at the site of this synthetic genetic inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Using these promising candidates, some applications of these UBPs in vitro and even in vivo have already been achieved in the past few years. 2,[5][6][7]10,21,[29][30][31][32][33][34][35][36][37][38][39][40] Apart from their basic functions to store and retrieve genetic information, the natural bases also exhibit some unique properties that make them ideal genetic materials, one of which is their excellent photostability against ultraviolet light. Such photostability can be attributed to the ultrafast deactivation of their excited states to ground states via conical intersections, therefore, dissipating the excessive energy obtained from excitation, as illustrated by extensive experimental and theoretical works.…”
Section: Introductionmentioning
confidence: 99%
“…Using these promising candidates, some applications of these UBPs in vitro and even in vivo have already been achieved in the past few years. 2,[5][6][7]10,21,[29][30][31][32][33][34][35][36][37][38][39][40] Apart from their basic functions to store and retrieve genetic information, the natural bases also exhibit some unique properties that make them ideal genetic materials, one of which is their excellent photostability against ultraviolet light. Such photostability can be attributed to the ultrafast deactivation of their excited states to ground states via conical intersections, therefore, dissipating the excessive energy obtained from excitation, as illustrated by extensive experimental and theoretical works.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it may be of importance that many chemotherapeutic drugs operate as DNA binders in tumor cells, [32][33][34] and thus affect the biological activity of the DNA. [35][36][37] For example, enzyme inhibition may be caused by occupation of the enzyme-binding sites with the drug or by significant changes of the DNA structure upon association of a ligand. In fact, some NIQ derivatives exhibit characteristic features of DNA-binding ligands, specifically an extended aromatic p system and amino and hydroxy functionalities that may establish attractive interactions in the DNA-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some NIQ derivatives exhibit characteristic features of DNA-binding ligands, specifically an extended aromatic p system and amino and hydroxy functionalities that may establish attractive interactions in the DNA-binding sites. [32][33][34][35][36] Moreover, these compounds possess a biaryl structure that may have the propensity to adapt to the helical structure of the nucleic acid and that has been shown also to cause preferential binding to abasic sitecontaining DNA, that is, DNA with an apyrimidinic or apurinic site, commonly referred to as AP-DNA. 38,39 Surprisingly, the DNA-binding properties of NIQs have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Subsequent synthetic and biochemical studies focused on understanding the properties of oligonucleotides containing the six-base genetic alphabet formed from A, C, G, T, P, and Z. [28][29][30][31] In a significant further development, Hoshika et al reported the simultaneous incorporation of B : S and P : Z into oligonucleotides, to generate DNA containing the eight-base genetic alphabet (A, T, C, G, P, Z, B, and S, Figure 1). This DNA possesses significantly enhanced information-storage capacity compared to the four-base natural alphabet, as well as the previouslyreported six-base alphabets based on the combination of canonical pairs with one of the Romesberg's hydrophobic pairs [9] or the Benner's P : Z pair.…”
Section: Introductionmentioning
confidence: 99%
“…On similar lines, G : C analog involving P (2‐aminoimidazo[1,2‐a]‐1,3,5‐triazin‐4(1H)‐one) and Z (4‐amino 5‐nitropyridin‐2‐one, Figure 1) was developed [28] . Subsequent synthetic and biochemical studies focused on understanding the properties of oligonucleotides containing the six‐base genetic alphabet formed from A, C, G, T, P, and Z [28–31] …”
Section: Introductionmentioning
confidence: 99%